Two-Phase Flow Modeling of Solid Dissolution in Liquid for Nutrient Mixing Improvement in Algal Raceway Ponds - Haider Ali; Dongda Zhang; Jonathan L. Wagner; Cheol Woo Park (Energies, 2018)
Achieving optimal nutrient concentrations is essential to increasing the biomass productivity of algal raceway ponds. Nutrient mixing or distribution in raceway ponds is significantly affected by hydrodynamic and geometric properties. The nutrient mixing in algal raceway ponds under the influence of hydrodynamic and geometric properties of ponds is yet to be explored. Such a study is required to ensure optimal nutrient concentrations in algal raceway ponds. A novel computational fluid dynamics (CFD) model based on the Euler–Euler numerical scheme was developed to investigate nutrient mixing in raceway ponds under the effects of hydrodynamic and geometric properties. Nutrient mixing was investigated by estimating the dissolution of nutrients in raceway pond water. Experimental and CFD results were compared and verified using solid–liquid mass transfer coefficient and nutrient concentrations. Solid–liquid mass transfer coefficient, solid holdup, and nutrient concentrations in algal pond were estimated with the effects of pond aspect ratios, water depths, paddle wheel speeds, and particle sizes of nutrients. From the results, it was found that the proposed CFD model effectively simulated nutrient mixing in raceway ponds. Nutrient mixing increased in narrow and shallow raceway ponds due to effective solid–liquid mass transfer. High paddle wheel speeds increased the dissolution rate of nutrients in raceway ponds.